2011
DOI: 10.1007/s00405-011-1757-x
|View full text |Cite
|
Sign up to set email alerts
|

Preserving bone conduction in patients with labyrinthine fistula

Abstract: The management of labyrinthine fistula is a controversial issue. Hearing preservation represents a major challenge. Retrospective study of 31 patients with labyrinthine fistula confirmed intra-operatively during cholesteatoma surgery. In all cases, total matrix removal was performed, and the fistula covered with bone dust, periostium and/or cartilage. Twenty-five patients received a high intra-operative dosage (500 mg) of intravenously applied steroids at least 15 min before handling the fistula. Outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Labyrinthine fistula is regarded as the most frequent complication of otitis media with cholesteatoma [ 6 , 11 ]. The management of a labyrinth fistula is challenging in itself and there are several other variables that add to that difficulty.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Labyrinthine fistula is regarded as the most frequent complication of otitis media with cholesteatoma [ 6 , 11 ]. The management of a labyrinth fistula is challenging in itself and there are several other variables that add to that difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…As the literature assumes that intravenous corticosteroids during the peeling of the cholesteatoma matrix of the labyrinth may be beneficial [ 2 , 10 , 11 , 18 ], we looked at this method in the light of our data. No statistical difference was found in literature search or in our direct comparison to the data of Jang et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that complete removal of the cholesteatoma matrix and fistula closure effectively control disease and preserve hearing [13,15] . According to these studies, if the matrix is left over the fistula site, the risk of labyrinthitis increases and sensorineural hearing loss or deafness may occur.…”
Section: Discussionmentioning
confidence: 99%